2004
DOI: 10.1080/00288233.2004.9513618
|View full text |Cite
|
Sign up to set email alerts
|

A review of emissions of methane, ammonia, and nitrous oxide from animal excreta deposition and farm effluent application in grazed pastures

Abstract: In pastoral soils, NH 3 and N 2 O gases are generated from N originating from dung, urine, biologically fixed N 2 , and fertiliser. The amount of these gaseous emissions depends on complex interactions between soil properties, climatic factors, and agricultural practices. In this review paper, the animal-excretal inputs and farm-effluent applications to New Zealand pastures are quantified. Data from overseas and New Zealand studies on CH 4 , NH 3 , and N 2 O emissions from excretal deposition and animal efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
156
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(173 citation statements)
references
References 137 publications
6
156
1
10
Order By: Relevance
“…Although not statistically different, median CH 4 concentrations measured from the loafing pen and open-lot (11 and 13 ppm v , respectively) trended higher than those in manure lane, bedding area, and compost piles. This was likely due to fermentation induced by the anaerobic environment of the loafing pen and open-lot pen, and anaerobic soil layers produced immediately under the manure's top surface [5]. The average CH 4 concentration was 0.36 ppm v from compost piles, which was lower than other sources, likely because the manure was already partially degraded.…”
Section: Methane Concentrationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although not statistically different, median CH 4 concentrations measured from the loafing pen and open-lot (11 and 13 ppm v , respectively) trended higher than those in manure lane, bedding area, and compost piles. This was likely due to fermentation induced by the anaerobic environment of the loafing pen and open-lot pen, and anaerobic soil layers produced immediately under the manure's top surface [5]. The average CH 4 concentration was 0.36 ppm v from compost piles, which was lower than other sources, likely because the manure was already partially degraded.…”
Section: Methane Concentrationsmentioning
confidence: 93%
“…Greenhouse gas emissions from livestock vary by animal type and growth stage due to different diets, feed conversion mechanisms, and the manure management [3]. Methane is produced by the microbes in the rumen of ruminant animals due to enteric fermentation, from freshly deposited manure due to bacterial processes, and from storage lagoons and settling basins due to anaerobic degradation [4][5][6]. Methane, with a global warming potential (GWP) of 25, can affect climate directly through its interaction with long-wave infrared energy and indirectly through atmospheric oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1) for the 'manure management' emission category. For example in NZ~1.3 of the 1.4 Mt of CO 2 -e/year of CH 4 from dairy farm manure comes from anaerobic ponds compared with just 0.1 Mt from manure deposited on pastures [determined from data in Saggar et al (2004)]. It is important to note that the term 'effluent pond' is used to encompass a wide range of systems from small (<100 m 3 ) pits with just a few weeks' effluent storage capacity to large (>2000 m 3 ) lagoons for up to 1 year's storage capacity.…”
Section: Ghg Emissions From Dairy Cattle 'Manure Management'mentioning
confidence: 99%
“…The knowledge of causes, magnitude, and mitigation potential of enteric CH 4 and soil N 2 O emissions is now well established for Australia, NZ, and overseas (de Klein et al 2001;Dalal et al 2003;Saggar et al 2004;Eckard et al 2010;Cottle et al 2011). By contrast, agricultural manure management emission estimates have not been verified by a rigorous review of the available literature since they were developed more than 15 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies conducted at the animal husbandry level in Switzerland (Staerfl et al, 2012;Zeitz et al, 2012) showed that using countryspecific EFs would not substantially alter the total estimate of livestock CH 4 emissions, high uncertainty remains, as differing farming practices can have significant impacts on the EFs (Lowry et al, 2001;Saggar et al, 2004;Christie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%